Optimization of benzyloxazoles as non-nucleoside inhibitors of HIV-1 reverse transcriptase to enhance Y181C potency - Bollini, Mariela (2012)
Design of non-nucleoside inhibitors of HIV-1 reverse transcriptase with improved activity towards Tyr181Cys containing variants was pursued with the assistance of free energy perturbation (FEP) calculations. Optimization of the 4-R substituent in 1 led to ethyl and isopropyl analogs 1e and 1f with 1–7 nM potency towards both the wild-type virus and a Tyr181C variant.